Hippocampal neuroplasticity and inflammation: relevance for multiple sclerosis. Issue 1 (December 2017) - Mancini, Andrea; Gaetani, Lorenzo; Di Gregorio, Maria; Tozzi, Alessandro; Ghiglieri, Veronica; Calabresi, Paolo; Di Filippo, Massimiliano
Abstract Cognitive impairment is very frequent during multiple sclerosis (MS), involving approximately 40–70% of the patients, with a profound impact on patient's life. It is now established that among the various central nervous system (CNS) structures involved during the course of MS, the hippocampus is particularly sensitive to the detrimental effects of neuroinflammation. Different studies demonstrated hippocampal involvement during MS, in association with depression and cognitive impairment, such as verbal and visuo-spatial memory deficits, even during the earlier phases of the disease. These cognitive alterations could represent the visible consequences of a hidden synaptic impairment. Indeed, neuronal and immune functions are intertwined and the immune system is able to modulate the efficacy of synaptic transmission and the induction of the main forms of synaptic plasticity, such as long term potentiation (LTP). Hippocampal synaptic plasticity has been studied during the last decades as the physiological basis of human learning and memory and its disruption can be associated with behavioral and cognitive abnormalities. The aim of the present work is to review the available evidence about the presence of hippocampal synaptic plasticity alterations in experimental models of MS, specifically during the course of experimental autoimmune encephalomyelitis (EAE) and to discuss their relevance with regard to human MS. Indeed, the failure of synapses to express plasticity during neuroinflammation could potentially lead to a progressive failure of the brain plastic reserve, possibly contributing to disability progression and cognitive impairment during MS.